Sexual dimorphism in morphometric characters of Mystus singaringan from Klawing River in Central Java, Indonesia: Strategic instruction for conservation development (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pramono TB, Arfiati D, Widodo MS, Yanuhar U. 2019. Sexual dimorphism in morphometric characters of Mystus singaringan from Klawing River in Central Java, Indonesia: Strategic instruction for conservation development. Biodiversitas 20: 1133-1139. This study aims to determine the sexual dimorphism of Mystus singaringan (Senggaringan fish) based on morphometric characters. The measurement of 24 morphometric characters in 30 M. singaringan from Klawing River was carried out using a digital caliper (0.01 mm). Morphometric data of M. singaringan analyzed using t-test have showed significant difference in 12 morphometric characters between sexes, such as standard length, head height, distance of the tip of the muzzle to eyes, distance of the tip of the muzzle to adipose fin, height of dorsal fin, height of pectoral fin, basic length of adipose fin, height of adipose fin, maximum height, length of first nasal barbel, length of first mandibular barbel, and length of second mandibular barbel. Analysis of growth of morphometric characters shows that there is a linear relationship between all morphometric characters and total length. The type of growth of all morphometric characters in both male and female M. singaringan is negative allometric.
Keywords: Sex Determination, Male, Female, Morphometric, Indigenous Species